0282 A cross-sectional study of markers of early immunological and cardiovascular health effects among a population exposed to carbon nanotubes: the CANTES study0282 A cross-sectional study of markers of early immunological and cardiovascular health effects among a population exposed to carbon nanotubes: the CANTES study. (23rd June 2014) - Vermeulen, Roel; Pronk, Anjoeka; Vlaanderen, Jelle; Hosgood, Dean; Rothman, Nat; Hildesheim, Allan; Silverman, Debra; Melis, Annemarie; Spaan, Suzanne; Voogd, Eef; Hoet, Peter; Godderis, Lode; et al.
Abstract : Objectives: To assess the association between occupational exposure to carbon nanotubes (CNTs) and early immunological and cardiovascular health effects. Method: We collected biological samples (blood, urine, buccal and nasal epithelium cells) from a group of workers in a CNT production factory and approximately age and sex matched unexposed individuals working in a different workplace. Based on an initial assessment of exposure data collected in the weeks before biological sampling we further classified CNT production workers as operators (high probability of exposure) and R&D workers (lower probability of exposure). We analysed blood samples for a panel of inflammatory markers. Results: We included 8 operators (median age 34.8), 16 R&D workers (median age 32.2), and 43 controls (median age 30.6). Preliminary analyses provide some evidence for an association between CNT exposure and selected cytokines. We observed a similar pattern when we restricted our analyses to non-smoking men. Concentrations of cytokines were exposure dependently upregulated with higher levels among operators than R&D workers; both higher than unexposed workers (p for trend <0.05). Conclusions: We observed some indications of early immunological health effects in a pilot study conducted among workers exposed to CNTs. Further analyses are planned, including assessment of lung function, heart rate variability, oxidative stress, and blood coagulation markers. Extensive exposure measurements were conducted in the CNT production factory as well and additional analyses will use these individual exposure measurements to more thoroughly explore exposure dependent effects.